2004
DOI: 10.1103/physreve.69.066304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of thermoacoustic energy conversion in a resonator

Abstract: Using thermoacoustic energy conversions, both amplification and damping of acoustic intensity are demonstrated. A differentially heated regenerator is installed near the velocity node of the resonator and thereby a high specific acoustic impedance and a traveling wave phase are obtained. It is shown that the gain of acoustic intensity resulting from the traveling wave energy conversion reaches 1.7 in a positive temperature gradient and 0.3 in a negative gradient. When the regenerator is replaced with a stack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 14 publications
2
37
0
3
Order By: Relevance
“…Therefore, the optimum amplitude pressure on the thermoacoustic prime mover engine this research generated by the length of tube resonator 180 cm. The research result similar to the studies has been conducted by Biwa [9]. Biwa has conducted research to know energy conversion performance thermoacoustic with two types of the stack.…”
Section: Resultssupporting
confidence: 69%
“…Therefore, the optimum amplitude pressure on the thermoacoustic prime mover engine this research generated by the length of tube resonator 180 cm. The research result similar to the studies has been conducted by Biwa [9]. Biwa has conducted research to know energy conversion performance thermoacoustic with two types of the stack.…”
Section: Resultssupporting
confidence: 69%
“…The impact of the Page 3 of 31 operating frequency and temperature difference between the stack ends on the refrigeration power was studied using network and thermodynamic models, as well as experimental approaches (Jebali et al, 2004). Another important strand of research involves looking at the physics of the thermoacoustic effect, for example the experimental demonstration of the thermoacoustic effect (Biwa et al, 2004) and the nonlinear acoustic streaming that often takes place in such systems (Bailliet et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Ueda et al [2] constructed a looped tube thermoacoustic prime mover and studied the acoustic fields generated by stacks with different ωτ. Biwa et al [3] demonstrated thermoacoustic conversions in the stack with ωτ = 0.13 and ωτ = 3.5 by making full use of the acoustic field induced in the resonator. Tsuji [4] reported a design for insertion position and channel radius of the stack in a thermoacoustic cooling system by considering ωτ parameter.…”
Section: Introductionmentioning
confidence: 99%